Flavonoids attenuate cancer metabolism by modulating Lipid metabolism, amino acids, ketone bodies and redox state mediated by Nrf2 - Samec, Marek; Mazurakova, Alena; Lucansky, Vincent; Koklesova, Lenka; Pecova, Renata; Pec, Martin; Golubnitschaja, Olga; Al-Ishaq, Raghad Khalid; Caprnda, Martin; Gaspar, Ludovit; Prosecky, Robert; Gazdikova, Katarina; et al. (European journal of pharmacology, 2023)
Metabolic reprogramming of cancer cells is a common hallmark of malignant transformation. The preference for aerobic glycolysis over oxidative phosphorylation in tumors is a well-studied phenomenon known as the Warburg effect. Importantly, metabolic transformation of cancer cells also involves alterations in signaling cascades contributing to lipid metabolism, amino acid flux and synthesis, and utilization of ketone bodies. Also, redox regulation interacts with metabolic reprogramming during malignant transformation. Flavonoids, widely distributed phytochemicals in plants, exert various beneficial effects on human health through modulating molecular cascades altered in the pathological cancer phenotype. Recent evidence has identified numerous flavonoids as modulators of critical components of cancer metabolism and associated pathways interacting with metabolic cascades such as redox balance. Flavonoids affect lipid metabolism by regulating fatty acid synthase, redox balance by modulating nuclear factor-erythroid factor 2-related factor 2 (Nrf2) activity, or amino acid flux and synthesis by phosphoglycerate mutase 1. Here, we discuss recent preclinical evidence evaluating the impact of flavonoids on cancer metabolism, focusing on lipid and amino acid metabolic cascades, redox balance, and ketone bodies.
Keywords: flavonoidy; metabolismus lipidů; Flavonoids; Humans; Lipid Metabolism; Ketone Bodies; Carcinogenesis; oxidace-redukce; NF-E2-Related Factor 2; ketolátky; lidé; nádorová transformace buněk; aminokyseliny; Amino Acids; Cancer cells; Metabolism; Neoplasms; Cell Transformation, Neoplastic; Metabolic reprogramming; faktor 2 související s NF-E2; nádory; Oxidation-Reduction